DISTRIBUSI KONSUMSI PANGAN ANTAR ANGGOTA RUMAH TANGGA PADA SAAT KRISIS EKONOMI DI DUA DESA IDT KABUPATEN SUBANG - Sri Prihatini; Syafrudin Syafrudin; Vita Kartika; Herman Sudiman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1999)
The Distribution Food Consumption Among The Family Members at Economic Crisis In Two IDT Villages In Subang District.The economic crisis in Indonesia has decreased the purchasing power of the families which further affected the household food consumption. The objective of this study is to observe the effect of economic crises on the intra-household food distribution, particularly the poor families. In other words, the objective of the study is to identify which of the family members that affected most by the crises. The socioeconomic status and food consumption data was collected from 100 households in two poor villages in the district of Subang, West Java. There were two rounds of data collection. The first data collection was carried out in August 1998 to represent the "paceklik" period, and the second data collection was carried out in November 1998 to represent the "harvest" period. The food consumption data of the individual family member was collected using "Weighing" method for two days. Nutrition intake was calculated based on Indonesian food composition table. The result showed that the energy and protein intake of individual family members in the periods of "paceklik" and "harvest" was still adequate (>90% RDA). The energy intake of all family members was not significantly different in two periods. However, there was a significant decrease in protein intake of the adult members from "paceklik" period to "harvest" period. While, for the underfives and school age children the protein intake was relatively stable in both periods. This study conclude that the most protected members of family in term of protein intake were children underfive years of age and school age children, whereas, the adult members were the most affected by the changes in the agricultural cycle.Keywords: Food Consumption, Economic Crises